Diluted Bitumen Affects Multiple Physiological Systems in Sockeye Salmon (Oncorhynchus nerka) Embryo to Juvenile Life Stages. (15th June 2022) - Lin, Feng; Alderman, Sarah L.; Gillis, Todd E.; Kennedy, Christopher J.
Abstract: An understanding of the risks associated with diluted bitumen (dilbit) transport through Pacific salmon habitat necessitates the identification and quantification of hazards posed to early life stages. Sockeye from the embryo to juvenile stage (8 months old) were exposed to four concentrations of the water‐soluble fraction of Cold Lake dilbit (summer blend; concentrations of 0, 13.7, 34.7, and 124.5 μg/L total polycyclic aromatic compounds). Significant mortality (up to 18% over controls) only occurred in the embryo to swim‐up fry stage. Impaired growth was seen in the alevin, swim‐up, and juvenile stages (maximum reduction 15% in mass but not fork length). Reductions in both critical (maximum 24% reductions) and burst (maximum 47% reductions) swimming speed in swim‐up fry and juveniles were seen. Alterations in energy substrate reserves (reductions in soluble protein and glycogen content, elevations in whole‐body lipid and triglyceride levels) at all stages may underlie the effects seen in swimming and growth. Dilbit exposure induced a preexercise physiological stress response that affected the recovery of postexercise biochemistry (cortisol, glycogen, lactate, triglyceride concentrations). The transcript abundance of the cytochrome P450 1A gene ( cyp1a ) was quantified in alevin head regions (containing the heart) and in the hearts of swim‐up fry and juveniles and showed a concentration‐dependent increase in the expression of cyp1a at all life stages. Environ Toxicol Chem 2022;41:1937–1949. © 2022 SETAC